2021
DOI: 10.1016/j.bja.2021.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Induced normothermia ameliorates the procoagulant host response in human endotoxaemia

Abstract: Background: Dysregulation of coagulation occurs commonly in sepsis, ranging from mild coagulopathy with decreased platelets to disseminated intravascular coagulation (DIC). We investigated the effect of induced normothermia on coagulation during lipopolysaccharide (LPS)-induced endotoxaemia in healthy volunteers. Methods: Twelve volunteers received an infusion of bacterial lipopolysaccharide (Escherichia coli; 2 ng kg À1 ) and were assigned to either induced normothermia or control. Induced normothermia to mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Extracellular histones have been proposed as significant mediators in sepsis pathogenesis, with several experiments demonstrating that extracellular histones can induce endothelial cell injury and impaired coagulation (5,33). In mouse models, intravenous histone administration provokes perturbations in the coagulation system similar to sepsis-induced consumptive coagulopathy and DIC, including endothelial damage, increased concentrations of TF and vWf, subsequently leading to PLT activation, extensive thrombosis, and coagulation factor depletion, thereby presenting as low PLT counts and prolonged PT and aPTT (2,24,(34)(35)(36). One study reported that circulating histone levels were higher in septic patients who developed DIC (6); however, the relationship between histones and various significant coagulation parameters (e.g., PLT counts, PT, aPTT, D-dimer, and fibrinogen) remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extracellular histones have been proposed as significant mediators in sepsis pathogenesis, with several experiments demonstrating that extracellular histones can induce endothelial cell injury and impaired coagulation (5,33). In mouse models, intravenous histone administration provokes perturbations in the coagulation system similar to sepsis-induced consumptive coagulopathy and DIC, including endothelial damage, increased concentrations of TF and vWf, subsequently leading to PLT activation, extensive thrombosis, and coagulation factor depletion, thereby presenting as low PLT counts and prolonged PT and aPTT (2,24,(34)(35)(36). One study reported that circulating histone levels were higher in septic patients who developed DIC (6); however, the relationship between histones and various significant coagulation parameters (e.g., PLT counts, PT, aPTT, D-dimer, and fibrinogen) remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium (Mg 2+ ) is an essential nutrient that maintains normal cellular physiological activity and homeostasis in the body through more than 300 biochemical reactions (8,9). Previous studies on Mg 2+ and magnesium sulfate (MgSO 4 ) have shown an anticoagulant effect with reduced PLT aggregation, blood clotting, and thrombosis (2,(10)(11)(12). A retrospective observational study has hinted that low Mg 2+ levels are associated with active coagulation and inhibition of fibrinolysis in septic patients; however, whether Mg 2+ is a factor affecting coagulation in sepsis is unclear (13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…), etc., which revealed that some of the most common autoantigen targets in COVID-19-associated coagulopathies, such as CL, PF4 and β2GP, have significant mimics with these bacteria but do not have significant mimics with SARS-CoV-2 and especially its spike protein [ 40 ] (summarized in Figure 1 ). Since some bacterial infections, especially GAS , Staphylococci, Klebsiella and Clostridia , are themselves associated with increased risks of coagulopathies [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], these results suggested that preceding or concomitant bacterial co-infections may support the induction of a variety of COVID-19 autoimmune coagulopathies through anamnestic secondary cross-reactivity or bystander activation of complementary autoimmune mechanisms to those activated by SARS-CoV-2. Conversely, if a pre- or co-existing bacterial infection were necessary to induce autoimmune coagulopathies, then the absence of such infections among the vast majority of vaccinees might explain the extremely infrequent occurrence of vaccine-induced thrombotic events [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%